A Critical Review of the Hydrometallurgy and Pyrometallurgical Recovery Processes of Platinum Group Metals from End-of-Life Fuel Cells - Sinikiwe A. Mvokwe; Opeoluwa O. Oyedeji; Mojeed A. Agoro; Edson L. Meyer; Nicholas Rono (Membranes)
Recently, the recovery of metals extracted from the spent membrane electrode assemblies (MEAs) of fuel cells has attracted significant scientific attention due to its detrimental environmental impacts. Two major approaches, i.e., pyrometallurgical and hydrometallurgical, have been explored to recover platinum group metals (PMGs) from used proton exchange membrane fuel cells (PEMFCs). However, the efficacy of these methods has been limited by the low concentrations of the metals and the high costs involved. Essentially, pyrometallurgical processes result in the evolution of harmful gases. Thus, the hydrometallurgical process is preferred as a suitable alternative. In this review, an overview of the application of pyrometallurgical and hydrometallurgical methods in the recovery of PGMs is presented. The health risks, benefits, and limitations of these processes are highlighted. Finally, the hurdles faced by, opportunities for, and future directions of these approaches are identified. It is envisaged that this review will shed light on the current status of processes for the recovery of spent PGMs and propel their advancement for effective recycling strategies.